PEMBERDAYAAN MASYARAKAT DALAM PEMBUATAN BIOGAS DARI KOTORAN SAPI - Kuntang Winangun; Wawan Trisnadi Putra (Studi Kasus Inovasi Ekonomi, 2018)
Agricultural and livestock products produce byproducts that have not received much attention, even considered as untreated waste. In general, the waste is used as manure. In fact, from agricultural waste and animal husbandry can be used as an alternative energy source, namely from biomass. One of the efforts to utilize livestock waste is to use it to produce fuel by using biogas technology. Biogas technology provides opportunities for rural communities, especially Rejomulyo Village, West District Magetan District which has a livestock business, both individual and group, to meet the needs of daily energy independently. The potential for biogas development in Rejomulyo village is quite large. That's because quite a lot of cows are kept by the community Rejomulyo village with the number of cows per 1 house about 1-2 tail. Each 1 cow / buffalo can produce approximately 2 m3 biogas / day. Implementation of biogas technology in areas that have farms can provide economic benefits if the design is appropriate in terms of technical and operational